Biogeochemical reappraisal of the freshwater–seawater mixing‐zone diagenetic model. Issue 5 (7th April 2021) - Petrash, Daniel A.; Bialik, Or M.; Staudigel, Philip T.; Konhauser, Kurt O.; Budd, David A.
Abstract: First proposed nearly half a century ago, the mixing‐zone model of dolomitization enjoyed a brief stay in the limelight before falling out of favour. Despite extended past criticism, arguments that build on its current validity are presented and discussed. The coastal mixing zone can be seen as an aquifer system exhibiting marked physicochemical gradients, reflective of the admixture of low salinity freshwater and seawater sources with variable redox potentials. This perspective requires a more holistic look at the mixing zone, not only as a gradient of major element concentrations, but also as the locus of enhanced subsurface redox sensitive reactions that occur at the pore‐space scale within a moveable diagenetic front. Combined genomic and isotopic data indicate that an active subsurface biosphere thrives in the mixing zone. This could facilitate Mg 2+ dehydration, generate alkalinity, consume protons and mobilize potentially catalyzing ions (i.e. Mn and Zn), which are all low temperature factors thought to promote dolomite formation from soluble precursors. In the updated model, the advective mix of fluids with contrasting composition modulate a range of biogeochemically induced mineral dissolution and reprecipitation reactions. Biotic and abiotic interactions between these fluids affect carbonate equilibrium and result in dissolution of soluble aragonitic and calcitic phases, while dolomite precipitates (as cement) and neomorphic replacement. The secondary dolomite often exhibits compositional heterogeneity and contentious δ 18 O signatures indicative of re‐equilibration. The role of manganese, zinc, intermediate sulphur species and ammonia are far from being fully understood, nor is their fingerprint in ancient deposits. Application of in situ spectroscopic imaging techniques, clumped and metal isotope analyses, as well as a more extended use of traditional approaches, such as sulphur isotopes, are poised to open many opportunities to further explore the biogeochemistry of this diagenetic environment and how it relates to platform dolomitization.